Sosialisasi Pembuatan Pupuk Organik Cair Di Desa Pisang Indah, Bumi Agung, Way Kanan, Lampung - Wawan Abdullah Setiawan; Paul Benyamin Timotiwu; John Hendri; Andi Setiawan (CV. Multi Kreasi Media, 2024)
The majority of people in Pisang Indah Village, Bumi Agung District, Way Kanan Regency, Lampung Province, are farmers. In farming, they use chemical fertilizers. Unfortunately, continuous use of chemical fertilizers can result in decreased soil quality and damage to soil structure. In order to replace chemical fertilizers with more affordable and ecologically friendly alternatives, socialization is being carried out on the manufacturing of Liquid Organic Fertilizer (Pupuk Organik Cair/POC) based on Local Microorganisms (Mikroorganisme Lokal/MOL). POC which comes from the fermentation of natural organic materials has become the main focus in efforts to increase plant productivity in a sustainable manner. This activity uses a descriptive-explanatory qualitative approach so that it presents practical steps to produce environmentally friendly and effective POC based on banana stems and rice washing water as an alternative fertilizer. The focus on the use of local organic materials, such as banana stems and rice washing water, is driving the adoption of sustainable agricultural practices in various agricultural communities. Through outreach activities and practical training, this article highlights farmers' interest and enthusiasm for POC as an alternative fertilizer that has the potential to provide good crop yields without damaging the environment. With the use of POC, it is hoped that in the future it can become the basis for efforts to empower farming communities in sustainable natural resource management to strengthen sustainable food security.